On Subjectivity and the Relationship with the Other: Qualitative Results of an Interview‐Study with 50 Young Muslims. (5th December 2021) - Kaiser, Paul Maximilian; Barth, Lena; Tuncel Langbehn, Gonca; Ruettner, Barbara; Goetzmann, Lutz
Abstract : The purpose of this paper is to investigate the relationship between subjectivity and the other during the course of integration among 50 young Muslims of dual national heritage in Germany. The largest group of migrants within Germany are people of Turkish and Kurdish origin. During the summer and autumn of 2018, we interviewed 50 individuals of both genders aged between 18 and 25. The interviews were carried out and evaluated in North Germany. We saw that the 'feeling of being held', 'being‐able‐to‐process‐(negative)‐experiences' and 'to take responsibility for oneself and other' are characteristics of well‐educated young Muslims. Those who feel at home in their Turkish family or in the Islamic religion are able to process positive and negative experiences and present more (mature) super‐ego structures. This allows them to be able to deal with the challenges of migration and integration. Based on the data, we developed the 'Triadic Model of Integration' within the Lacanian L‐Scheme of Subjectivity.